ANALISIS STRATEGI CINA MELALUI TEKNIK PENYAJIAN MEDIA SEBAGAI ALAT PROPAGANDA DALAM ISU REUNIFIKASI TAIWAN - Taufik, Taufik; Azahro, Anggun (Jurnal Studi Diplomasi dan Keamanan, 2026)
The Taiwan reunification dispute, based on the One-China Policy, continues to be a strong ambition for China. Chinese President Xi Jinping has asserted that nothing can prevent China from achieving reunification, and this has become a strong reason for China to launch various strategies that not only take the form of intervention but also through propaganda manipulation in the media. Media has become a powerfull instrument of interests in China, serving as an influence machine for the Party and an agent of relational propaganda production between information authoritarianism and control over the growth of influence connected to the strategic agenda. Through the media, propaganda is packaged as a tool that has been designed to influence the spread of belief in Taiwan-China reunification. And choose reunification as a future ideal that must be realized from the perspective of mainland China's side. This study attempts to analyze the media agenda through the method of presenting propaganda on the issue of Taiwan reunification. The author observes that China has implemented a collaborative strategy between the use of issue framing, nicknames selection, and specific delivery models, all of which point to several propaganda techniques used as a tool to manipulate Taiwan reunification. However, for specific influence and outcomes, the research dimension still needs to be developed